Pengaruh Penerapan Model Pembelajaran Berbasis Project Citizen Terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII SMP NEGERI 16 Tebo Pada Mata Pelajaran PPKN - Pitri, Arnia; Anderson, Irzal (Civic Education Perspective Journal, 2023)
This research was motivated by the low critical thinking ability of students in Civics subjects which only reached a percentage of 40% "less critical". This is because the learning process provided by the teacher still uses the lecture and question and answer method. This causes many students to have difficulty in identifying questions, analyzing accurate information, conveying logical arguments and having difficulty in concluding a decision in each question. This study aims to determine the effect of the application of the project citizen-based learning model on students' critical thinking skills in PPKn VIII subjects at SMP Negeri 16 Tebo. This research uses a quantitative method with a true experimental design type of research. The research design used was Posttest Only Control Design. This research was conducted at SMP Negeri 16 Tebo. The results of this study were obtained, the average experimental class was 69.00 with the "critical" category of 69% and the control class average was 50.00 with the "critical enough" category 53%. After testing the hypothesis using the t-test, the value of tcount > ttable (6,256 > 2,001) with a level of 5%, which means the project citizen model has a positive influence on students' critical thinking skills and a sign (2-tailed) value is obtained on critical thinking skills. student is 0.000 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that, there is an effect of implementing the project citizen model on students' critical thinking skills.